Schaftoside Interacts With NlCDK1 Protein: A Mechanism of Rice Resistance to Brown Planthopper, Nilaparvata lugens - Hao, Pei-Ying; Feng, Ya-Lin; Zhou, Yi-Shen; Song, Xin-Mi; Li, Hong-Liang; Ma, Yan; Ye, Cheng-Long; Yu, Xiao-Ping (Frontiers in Plant Science, 2018)
Brown planthopper (BPH) Nilaparvata lugens Stål is a serious insect pest of rice in Asian countries. Active compounds have close relationship with rice resistance against BPH. In this study, HPLC, MS/MS, and NMR techniques were used to identify active compounds in total flavonoids of rice. As a result, a BPH resistance-associated compound, Peak 1 in HPLC chromatogram of rice flavonoids, was isolated and identified as schaftoside. Feeding experiment with artificial diet indicated that schaftoside played its role in a dose dependent manner, under the concentration of 0.10 and 0.15 mg mL-1, schaftoside showed a significant inhibitory effect on BPH survival (p < 0.05), in comparison with the control. The fluorescent spectra showed that schaftoside has a strong ability to bind with NlCDK1, a CDK1 kinase of BPH. The apparent association constant KA for NlCDK1 binding with schaftoside is 6.436×103 L/mol. Docking model suggested that binding of schaftoside might affect the activation of NlCDK1 as a protein kinase, mainly through interacting with amino acid residues Glu12, Thr14 and Val17 in the ATP binding element GXGXXGXV (Gly11 to Val18). Western blot using anti-phospho-CDK1 (pThr14) antibody confirmed that schaftoside treatment suppressed the phosphorylation on Thr-14 site of NlCDK1, thus inhibited its activation as a kinase. Therefore, this study revealed the schaftoside-NlCDK1 interaction mode, and unraveled a novel mechanism of rice resistance against BPH.